The improvement of an anti-CD22 immunotoxin: Conversion to single-chain and disulfide stabilized form and affinity maturation by alanine scan - Kawa, Seiji (Landes Bioscience, 2011)
HA22-LR is a recombinant immunotoxin for the treatment of B-cell malignancies that contains the Fv portion of an anti-CD22 antibody fused to a functional portion of Pseudomonas exotoxin A. In the present study, we attempted to improve this molecule. First, we produced a single-chain version of HA22-LR (scdsFv-HA22-LR) in which a peptide linker was introduced between the disulfide-linked light and heavy chains to enable production via single fermentation. No difference in cytotoxic activity was observed between scdsFv-HA22-LR and prototype HA22-LR. Next, we attempted to increase the affinity of scdsFv-HA22-LR by using alanine scanning mutagenesis of complementarity determining regions (CDRs) to assess the specific contribution of each CDR residue to the antigen binding. We found that mutation of asparagine 34 in V(L)CDR1, which is located at the V(L)/V(H) interface, to alanine (N34A) caused a substantial increase in affinity and activity. Estimated K(D) values measured by fluorescence-activated cell sorting were lowered by 10-fold: 0.056 nM in the N34A mutant compared to 0.58 nM in wild type (WT). Cell viability assays of CD22-positive B-cell lymphoma and leukemia cell lines showed that the N34A mutant had increased cytotoxicity ranging from ∼2 (HAL-1, IC(50)(WT): 2.37 ± 0.62 ng/ml, IC(50)(N34A): 1.32 ± 0.41 ng/ml) to 10 (SUDHL-6, IC(50)(WT): 0.47 ± 0.090 ng/ml, IC(50)(N34A): 0.048 ± 0.018 ng/ml)-fold compared to WT immunotoxin. The present study suggests that the N34A mutant of scdsFv-HA22-LR could have important consequences in a clinical setting.